2017
DOI: 10.1016/j.scitotenv.2016.12.098
|View full text |Cite
|
Sign up to set email alerts
|

Shipping emissions and their impacts on air quality in China

Abstract: China has >400 ports, is home to 7 of 10 biggest ports in the world and its waterway infrastructure construction has been accelerating over the past years. But the increasing number of ports and ships means increasing emissions, and in turn, increasing impact on local and regional air pollution. This paper presents an overview of the broad field of ship emissions in China and their atmospheric impacts, including topics of ship engine emissions and control, ship emission factors and their measurements, developi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(74 citation statements)
references
References 33 publications
3
60
1
Order By: Relevance
“…The NO x emissions from shipping activities are difficult to detect from space near Chinese coastal areas since the ship tracks are hidden in the outflow of NO 2 plumes from the mainland (see Figure 1a). Traditional ship inventories are often lacking information on these ship activities or have large uncertainties on their ship emissions (C. Wang et al, 2008;Y. Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NO x emissions from shipping activities are difficult to detect from space near Chinese coastal areas since the ship tracks are hidden in the outflow of NO 2 plumes from the mainland (see Figure 1a). Traditional ship inventories are often lacking information on these ship activities or have large uncertainties on their ship emissions (C. Wang et al, 2008;Y. Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The number of studies of shipping emissions on a regional scale in East Asia is limited, and most of them are at port or city level (Y. Zhang et al, 2017). The application of the data from the Automatic Identification System (AIS) significantly reduced uncertainties in bottom-up shipping emission inventories (Jalkanen et al, 2009 (Jalkanen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, the studies on shipping emissions in Asia are only limited to a few individual ports or regional studies. Zhang et al (2017). National-level or port cluster shipping emissions have not been reported until now.…”
Section: Introductionmentioning
confidence: 99%
“…According to Corbett et al (), nearly 70% of the ship's exhaust emissions occur within 400 km from the global coastline. Other studies found a 1–45% increase in local PM 2.5 concentrations due to ship emissions (Chen et al, ; Jeong et al, ; Liu et al, ; Tao et al, ; Viana et al, ; Yau et al, ; Zhang et al, ).…”
Section: Introductionmentioning
confidence: 92%